Characterization of Magnetorheological Fluid: A Study on Sedimentation and Redispersion. Issue 7 (27th January 2022) - Prajapati, Hiren; Lakdawala, Absar
Abstract : Herein, an induction method based setup for quantification of sedimentation behavior of magnetorheological fluids (MR fluids) consisting of 10% carbonyl iron powder in silicone oil is used. The effect of addition of Aerosil (stabilizer) on sedimentation is proposed with the help of "sedimentation index." The proposed model of sedimentation index is compared with experimental measurement and is found to be in good agreement. In case of unavoidable event of settling, the important point is the ease of redispersion of sediment. This is directly evaluated with the help of a slider crank mechanism based setup which is proposed on the basis of the actual application. The quantification of redispersibility of the settled MR fluid is proposed using novel "redispersion index." It is observed that increasing the concentration of Aerosil reduces the settling due to high off‐state viscosity, however, at the cost of redispersibility. In this study, the optimum trade‐off between the redispersibility and slow settling is obtained with 15% concentration of Aerosil in the MR fluid. Abstract : The proposed study quantifies the effect of Aerosil on sedimentation and redispersion of magnetorheological fluids (MR fluids). The induction method and slider crank mechanism based experimental setups are used to study the sedimentation and redispersion, respectively. The quantification of sedimentation and redispersion is proposed with the help of novel "sedimentation index" and "redispersion index."